2010
DOI: 10.1007/s10067-010-1572-6
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone pulse plus mizoribine in children with Henoch–Schoenlein purpura nephritis

Abstract: We evaluated whether methylprednisolone and urokinase pulse therapy combined with mizoribine (MUPM) was effective in children with severe Henoch-Schoenlein purpura nephritis (HSPN). We studied 12 patients who had been diagnosed with HSPN of at least ISKDC type III. All patients were treated with MUPM. Clinical features, pathological findings, and prognosis were prospectively investigated. Ten patients (responders; nine with ISKDC grade IIIb and one with grade IVb) were treated with MUPM, whereas MUPM was disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 20 publications
0
18
0
2
Order By: Relevance
“…The non -responders demonstrated continued high levels of urinary protein excretion after 3 months of therapy, and MUPM was discontinued. These results suggests that MUPM is effective in ameliorating proteinuria and the histological severity of HSPN in patients with <50% crescents, but is not so effective for HSPN in patients with >50% crescents 48) . On the other hand, Ninchoji et al retrospectively reported that patients with moderately severe HSPN (histological grade I -III and serum albumin [Alb] >2.5 g/dl), who were treated with angiotensinconverting enzyme inhibitors and/or angiotensin receptor blockers, showed resolution of proteinuria without renal dysfunction during the observation period (3.76±0.37 years).…”
Section: (2) the Efficacy Of Multiple -Drug Therapymentioning
confidence: 83%
“…The non -responders demonstrated continued high levels of urinary protein excretion after 3 months of therapy, and MUPM was discontinued. These results suggests that MUPM is effective in ameliorating proteinuria and the histological severity of HSPN in patients with <50% crescents, but is not so effective for HSPN in patients with >50% crescents 48) . On the other hand, Ninchoji et al retrospectively reported that patients with moderately severe HSPN (histological grade I -III and serum albumin [Alb] >2.5 g/dl), who were treated with angiotensinconverting enzyme inhibitors and/or angiotensin receptor blockers, showed resolution of proteinuria without renal dysfunction during the observation period (3.76±0.37 years).…”
Section: (2) the Efficacy Of Multiple -Drug Therapymentioning
confidence: 83%
“…Overall, these observations suggest that MPNS pulses should be used preferentially at the initiation of the steroid treatment. A favorable role of initial high dosage of steroids is suggested by other noncontrolled studies (125)(126)(127)(128).…”
Section: Crescent Formationmentioning
confidence: 96%
“…Re-cent papers have reviewed studies on HSPN therapy (96 -98). Several types of treatments have been claimed to be efficacious in severe forms of HSPN in noncontrolled studies: MPNS followed by prednisone (124,126), plasma exchange alone (109,110), or corticosteroids (prednisone with or without initial MPNS) combined with urokinase (125) or with immunosuppressive drugs such as cyclophosphamide, azathioprin, and mizoribin (124,(127)(128)(129)(130). The value of the latter series might be controversial because spontaneous recovery is not excluded when patients are compared with themselves.…”
Section: Actual Choice For the Clinicianmentioning
confidence: 99%
“…In the RCT of Pillebout et al [24], the small number of patients with at least ISKDC grade III (<30 %) might have been insufficient to evaluate the efficacy of CPH in patients with extra-capillary proliferation and result in a significant difference with the control group that received the same steroid treatment (MP pulses followed by oral prednisone). By contrast, the results of one non-randomized prospective trial and several retrospective studies suggest the efficacy of immunosuppressive drugs in association with steroid protocols including MP pulses in severe cases of HSPN [26][27][28][29][30].…”
Section: Comment On the Use Of Immunosuppressive Drugsmentioning
confidence: 91%
“…In summary, we suggest that clinicians should not be prone to use oral prednisone alone in cases of grade III with extensive inflammatory lesions for the following reasons: (1) the risk of evolution to CKD even in ISKDC classification grade III [2]; (2) a better effect of MP pulses associated with oral prednisone compared with oral prednisone alone in the case of glomerular inflammation; (3) the negative reports on the beneficial effects of prednisone alone in retrospective case series [5,[20][21][22]; (4) a possible beneficial effect of MP pulses followed by prednisone suggested in a prospective case series compared to a historical series of the same centre [15] and in the control arm of one RCT [24]; (5) the beneficial effect of MP pulses suggested in multiple drug schemas [25][26][27][28][29][30].…”
Section: Comment On the Use Of Steroidsmentioning
confidence: 99%